HOMAGE TO HENRI DUTILLEUX - Alexandra MARINESCU (Studia Universitatis Babeş-Bolyai. Musica, 2023)
Henri Dutilleux was one of the prominent figures of European composition, especially in the second half of the 20th century. A complex personality, he worked throughout his career as a musician in various poses, from pianist, to accompanist, to conductor, to pedagogue, to composer, being one of the main promoters of French culture and beyond. He received numerous awards and recognitions for his entire activity, his reputation not only surpassing the borders of the country, but also the European ones. Although he began composing at a very young age, Dutilleux repeatedly omits to include these works in his catalog, even refusing to mention them in the section of his interpreted works. Meticulous and extremely pedantic, he always made changes to his works, constantly crystallizing his style both throughout the varied musical experiences in which the musician took part and through the close collaborations he had with instrumental artists whom he consulted regarding timbral possibilities and techniques of the instruments he was writing for. His compositions, although not very numerous, encompass a vast genuistically variety, and an exhaustive stylistic approach. Although he always embraces new compositional techniques, Dutilleux never reaches a rational extremism, keeping in the foreground the idea of meaningful music, and not the other way around. He died on 22nd of May 2013, in Paris, at the age of 97.